Gene-Based Therapeutics for Acquired Retinal Disease: Opportunities and Progress - Tan, Tien-En; Fenner, Beau James; Barathi, Veluchamy Amutha; Tun, Sai Bo Bo; Wey, Yeo Sia; Tsai, Andrew Shih Hsiang; Su, Xinyi; Lee, Shu Yen; Cheung, Chui Ming Gemmy; Wong, Tien Yin; Mehta, Jodhbir Singh; Teo, Kelvin Yi Chong (Frontiers in Genetics, 2021)
Acquired retinal diseases such as age-related macular degeneration and diabetic retinopathy rank among the leading causes of blindness and visual loss worldwide. Effective treatments for these conditions are available, but often have a high treatment burden, and poor compliance can lead to disappointing real-world outcomes. Development of new treatment strategies that provide more durable treatment effects could help to address some of these unmet needs. Gene-based therapeutics, pioneered for the treatment of monogenic inherited retinal disease, are being actively investigated as new treatments for acquired retinal disease. There are significant advantages to the application of gene-based therapeutics in acquired retinal disease, including the presence of established therapeutic targets and common pathophysiologic pathways between diseases, the lack of genotype-specificity required, and the larger potential treatment population per therapy. Different gene-based therapeutic strategies have been attempted, including gene augmentation therapy to induce in vivo expression of therapeutic molecules, and gene editing to knock down genes encoding specific mediators in disease pathways. We highlight the opportunities and unmet clinical needs in acquired retinal disease, review the progress made thus far with current therapeutic strategies and surgical delivery techniques, and discuss limitations and future directions in the field.